The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajpgi.00229.2016
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxylase inhibition regulates inflammation-induced intestinal fibrosis through the suppression of ERK-mediated TGF-β1 signaling

Abstract: Fibrosis is a complication of chronic inflammatory disorders such as inflammatory bowel disease, a condition which has limited therapeutic options and often requires surgical intervention. Pharmacologic inhibition of oxygen-sensing prolyl hydroxylases, which confer oxygen sensitivity upon the hypoxia-inducible factor pathway, has recently been shown to have therapeutic potential in colitis, although the mechanisms involved remain unclear. Here, we investigated the impact of hydroxylase inhibition on inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…In recently published work, we described a role of hydroxylase inhibition as a negative regulator of transforming growth factor-β1–induced intestinal fibrosis. These effects were HIF independent and appear to be caused by hydroxylase-dependent modulation of the noncanonical transforming growth factor–extracellular regulated kinase signaling pathway 157 . Given the relevance of the extracellular regulated kinase pathway in fibrotic pathology, these observations may represent a first step toward investigating hydroxylase inhibition as antifibrotic therapy in IBD 158, 159, 160…”
Section: Hydroxylase Inhibitors: a New Therapeutic Approach In Ibdmentioning
confidence: 89%
“…In recently published work, we described a role of hydroxylase inhibition as a negative regulator of transforming growth factor-β1–induced intestinal fibrosis. These effects were HIF independent and appear to be caused by hydroxylase-dependent modulation of the noncanonical transforming growth factor–extracellular regulated kinase signaling pathway 157 . Given the relevance of the extracellular regulated kinase pathway in fibrotic pathology, these observations may represent a first step toward investigating hydroxylase inhibition as antifibrotic therapy in IBD 158, 159, 160…”
Section: Hydroxylase Inhibitors: a New Therapeutic Approach In Ibdmentioning
confidence: 89%
“…14 In fact, it could recently be shown that pharmacologic pan-hydroxlase inhibition significantly attenuated the development of intestinal fibrosis in mice exposed to experimental colitis. 47 However, because most of these drugs are neither specific for the oxygen-sensing PHD enzymes (PHD1, PHD2, and PHD3) nor for distinct cell populations, it remains to be investigated whether pharmacologic PHD enzyme inhibitors can be applied to rather specifically target PHD1 in HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Acting upon human SEMFs, TGF-β enhances their migratory capacity and increases production of collagen and TIMP-1 [13,35,51]. TGF-β blockade ameliorated fibrosis in animal models of chronic colitis [52], whereas overexpression of TGF-β leads to intestinal stricture formation [53]. In a newly established model for fibrosis using human intestinal organoids, TGF-β treatment resulted in upregulation of fibrosis-related factors, such as collagen type I, fibronectin, α-SMA, actin contractile gene MYLK and fibrogenic transcription factor MLK1 [54].…”
Section: From Endothelial and Epithelial Injury To Myofibroblast Actimentioning
confidence: 99%